Report of the Task Force the Delhi-Mumbai and Delhi-Howrah Freight Corridors - Planning Commission (Planning Commission, 2006)
This Report responds to the direction of the Committee on Infrastructure, chaired by the Prime Minister, to prepare a concept paper on the Delhi-Mumbai (Western) and Delhi-Howrah (Eastern) dedicated freight corridor projects, and to suggest a new organisational structure for planning, financing, construction and operation of these corridors. The Task Force, constituted for this purpose, was chaired by Shri Anwarul Hoda, Member, Planning Commission and included experts and representatives from the Railway Board, Planning Commission and Ministry of Finance. The recommendations made in this Report were approved by the Committee on Infrastructure on February 16, 2006 and their implementation has commenced.
Planning Commission Government of India
Planning Commission Government of India